Environmental Factor Contributed to The Onset of Schizophrenia - Yuleni Yuleni; Tuti Wahmurti A. Sapiie; RA. Retno Ekowati (Althea Medical Journal, 2017)
Background: Schizophrenia is a severe and chronic mental disorder that needs a long term treatment and social support. This condition may results in burden and disturbance in the family and society A number of studies have investigated some environmental factors that may potentially lead to schizophrenia. One of many suspected environmental factors is place of born or grew up. This study was conducted to investigate association between place of born or grew up and age of onset of schizophrenia.Methods: This analytical study using cross-sectional method was conducted by retrieving data from 72 medical records of hospitalized schizophrenic patients in Dr. Hasan Sadikin General Hospital from October‒November 2013.  The variables in this study were age of onset and place (urban or rural) where the patients born or grew-up.The collected data were analyzed using Chi-Square statistical test.Results: This study discovered that 75% of subjects were born or grew up in urban area, 68% of subjects had age of onset at 20‒40 years and there was no association between place of born or grew up and age of onset of schizophrenia (p-value was 0.108).Conclusions: More than half subjects were born and grew up in urban, who had age of onset of schizophrenia at 20‒40 years and there is no significant association between place of born or grew up and age of onset of schizophrenia. DOI: 10.15850/amj.v4n2.1080